Representamen, Object, dan Interpretant dalam Film Bulan Terbelah di Langit Amerika Karya Rizal Mantovani: Sebuah Analisis Semiotika - Nur Annisa, Bening; Sakinah, R. Myrna Nur (TEXTURA, 2020)
This article discusses the analysis of representamen, object, and interpretant which are the core elements of Charles Sanders Pierce’s Semiotic Theory in a film entitled Bulan Terbelah di Langit Amerika. The science of Semiotics used in this study serves as a basis for interpreting the signs found into a clear meaning. By using the descriptive qualitative method, the researcher analyzes the hidden meaning signs in the Bulan Terbelah di Langit Amerika directed by Rizal Mantovani. The researcher uses the data found in the film and then analyzes it to be able to interpret it using Pierce’s Semiotic Theory. The results of the research conducted, the researcher found hidden meanings that can be interpreted through scenes, characters, and properties used in the film. These found meanings are also related to the theme raised in this film, which is about how Islam is in America after the 9/11 tragedy.